Interfaith Marriage in Contemporary Islamic Family Law: Analysis of 2005 Indonesian Ulama Council (MUI) Fatwa Number 4 about Interfaith Marriage based on the Theory of Al-Maslahah Al-Mursalah - Burhanudin, M.; Budi Wibowo, Muhammad Kurniawan; Pradana, Aditya Fajri Kurnia (Tasyri' : Journal of Islamic Law, 2025)
Purpose – This study aims to investigate the Fatwa of the 2005 Indonesian Ulama Council (MUI) Number 4 on interfaith marriage, which is based on al-Maslahah al-Mursalah theory, and determine its relevance and contribution to community well-being. This study will investigate how the Indonesian Ulama Council (MUI) sees interfaith marriage and how this fatwa can help achieve benefits while avoiding harm in national life. Methods – This study employs library research methods with a normative approach, with literature data serving as the primary source. In this case, the study focuses on the Indonesian Ulama Council (MUI) Fatwa No. 4 of 2005 on Interfaith Marriages, which is based on the al-Maslahah al-Mursalah theory. Findings – The findings of this study indicate that MUI strictly prohibits interfaith marriage because can destroying faith, social cohesion and family harmony. Several scholar such as Hamka, Quraish Shihab and Musdah Mulia have diverse opinions about interfaith marriages, reflects wider debates regarding modernity in the context of Islamic Law. This research confirms the relevance of fatwas in dealing with contemporary issues while maintaining religious principles and societal dynamics. Research limitation – This research is limited to a normative study regarding the MUI fatwa on interfaith marriage and the role of this fatwa in maintaining public welfare. Given these limitations, future research is expected to expand on the findings of this study by employing an empirical approach that integrates other sciences.